Profiling of physical activity usage in selected urban green spaces - Ty, Trizsa Jasmin C. 2000-; Dimarucut, Alberto (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Urban green spaces (UGS) play a critical role in providing opportunities for physical activity (PA) in urbanized cities. This observational, cross-sectional study aims to profile two selected UGS, namely Marikina River Park and Marikina Heights Park Complex, in Marikina City in the context of their utilization for physical activity and recreation. Interviews with two government officials were conducted to collect data about the historical background of the selected parks. Systematic observation using the SOPARC tool was used to observe park visitors and their physical activity for 4 days in each park. Findings from the interviews show that the selected UGS was built for the purpose of community and personal development. Observation shows that of 6948 total park visitors, the majority use the UGS for PA (47.91% moderate PA and 3.74% vigorous PA) while 48.34% participate in sedentary behavior. The majority of park visitors are male and the most observed age group present are teenagers followed by adults, children, and lastly, the elderly. Various types of PA were observed in the park with walking, biking, and dancing being the most common activities. These findings suggest that the selected UGS was built to be used for PA to fulfill its initial purpose. However, there is a need for more improvements to encourage the less observed demographic groups to visit the UGS. Built environment and organized activity were observed to appeal to specific demographics of park visitors. Organized activity can be key to encouraging PA among certain demographics without area improvements.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Keywords: Public spaces; Exercise; Recreation areas